Reconstruction of Character Education in the Global Era (Ibnu Miskawaih Concept Analysis Study) - Nur Zaidi Salim; Maragustam Siregar; Mufrod Teguh Mulyo (Journal Research of Social Science, Economics, and Management, 2022)
Character education is an urgent education because considering the moral crisis that occurs on all fronts in the era of globalization, in addition, the impact caused by this era of globalization and information has positive and negative impacts, such as in Indonesia, which is currently experiencing a crisis and lacks figures who can be used as an example, because many public figures are now committing crimes such as corruption, collusion, prostitution, and so on. Ibn Miskawaih is one of the prominent Islamic philosophers who touched the concept of character education which is famous in his book Tahzib al-akhlak wa tathir al-a'raf. This study aims to describe and analyze: (1) the concept of Ibn Miskawaih's character education (2) the reconstruction of character education in the global era (Ibn Miskawaih's concept analysis). This research is library research that refers to primary literature including the book of Tahdzibul Akhlaq (Ibnu Miskawaih), secondary library books, relevant books, journals, and documents. This study uses a qualitative approach in addition, objective and pragmatic, with the method of content analysis. Drawing conclusions using the deductive method. The results showed that: The concept of Ibn Miskawaih's character is, namely The Golden (The Doctrine of The Mean). He stated that human character is built on four foundations, namely self-restraint, courage, wisdom, and justice. Viewing education as a means of inculcating noble character, humanizing humans, socializing individuals, and inculcating shame, must be reconstructed in the current global era so that it can be used as human nature or the result of exercises in order to make a good character.